Evaluation : objective process that has influenced the subjectivity. (2022)
Evaluate, is undoubtedly a word that evokes a feeling in the subject from the position from which it must be assumed. For some it represents note, for others capacity, for others power and surely in a journey through the experience and the roles or various places that it occupies, a new conception or a new nuance regarding it will be given, which has as others a close relationship when it comes to putting on the scene the school process, the teaching process, and takes on some unique connotations when this process is installed in the formal education of the Basic, central axis of this writing, which does not intend but to retake it from reflective way, in order to try a new look at what it can mean. So, to achieve the exposed reflection, initially it could be located in a time and a space, which begins to be noticed without a doubt, as old as being itself in a social recognition of relationships, since each group of people from what is rescues in different narratives, realizes that the human being tried to measure and compare.